PELATIHAN PEMBUATAN VIDEO PEMBELAJARAN BERBASIS POWTOON SEBAGAI ALTERNATIF MEDIA PEMBELAJARAN PADA GURU SMP-TQ MU’ADZ BIN JABAL KENDARI - Takda, Amiruddin; Tahang, La; Sukariasih, Luh; Sahara, La; Nursalam, La Ode (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2021)
Activities seek to improve the awareness and information of teachers about the role of educational media in Junior High School learning activities. Furthermore, this curriculum also teaches SMP TQ-Mu'adz Bin Jabal teachers to use the Powtoon technology to design and render instructional videos. Increasing teacher imagination in the creation and use of video learning media is the specific goal to be accomplished, so that science learning in schools can be more contextual. The method used in implementing this Community Service is counselling, training, and question and answer methods. This activity begins with observations in schools and related institutions/agencies in the first week, followed by core activities at SMP TQ-Mu'adz Bin Jabal Kendari. From the results of the dedication, it was found that: (1). This activity has been able to increase teacher knowledge about the urgency of instructional media and the development of forms of instructional media, especially those related to technological developments; (2) This activity has been able to improve the ability of teachers to operate computers or laptops, including in making online-based learning videos that are integrated into Powtoon.